HOMELESS WITH SCHIZOPHRENIA PRESUMPTIVE DISABILITY PILOT EVALUATION. - Stegman Bailey, Michelle; Goetz Engler, Debra; Hemmeter, Jeffrey (Social Security Bulletin, 2016)
Many homeless individuals with a serious mental illness are potentially eligible for Supplemental Security Income (SSI) payments, but the nature of their impairment poses obstacles to completing the SSI application process. In this article, we evaluate the Homeless with Schizophrenia Presumptive Disability (HSPD) pilot that tested whether providing support during the application process improves SSI application outcomes—such as increasing the allowance rate and shortening the time to award—in selected communities in California. Importantly, the HSPD pilot included a presumptive disability determination that provided up to 6 months of SSI payments before an award. Relative to the comparison groups chosen in the surrounding geographic areas, in an earlier period, and in the same locations, we found that the pilot intervention led to higher allowance rates at the initial adjudicative level, fewer requests for consultative examinations, and reduced time to award. We also discuss policy options for this population.